The MICOS Complex Subunit Mic60 is Hijacked by Intracellular Bacteria to Manipulate Mitochondrial Dynamics and Promote Bacterial Pathogenicity - Changyong Cheng; Mianmian Chen; Jing Sun; Jiali Xu; Simin Deng; Jing Xia; Yue Han; Xian Zhang; Jing Wang; Lei Lei; Ruidong Zhai; Qin Wu; et al. (Advanced Science)
Abstract Host mitochondria undergo fission and fusion, which bacteria often exploit for their infections. In this study, the underlying molecular mechanisms are aimed to clarify through which Listeria monocytogenes (L. monocytogenes), a human bacterial pathogen, manipulates mitochondrial dynamics to enhance its pathogenicity. It is demonstrated that L. monocytogenes triggers transient mitochondrial fission through its virulence factor listeriolysin O (LLO), driven by LLO's interaction with Mic60, a core component of the mitochondrial contact site and the cristae organizing system (MICOS). Specifically, Phe251 within LLO is identify as a crucial residue for binding to Mic60, crucial for LLO‐induced mitochondrial fragmentation and bacterial pathogenicity. Importantly, it is that Mic60 affect the formation of F‐actin tails recruited by L. monocytogenes, thereby contributing to intracellular bacterial infection. Mic60 plays a critical role in mediating changes in mitochondrial morphology, membrane potential, and reactive oxidative species (ROS) production, and L. monocytogenes infection exacerbates these changes by affecting Mic60 expression. These findings unveil a novel mechanism through which intracellular bacteria exploit host mitochondria, shedding light on the complex interplay between hosts and microbes during infections. This knowledge holds promise for developing innovative strategies to combat bacterial infections.